HATE SPEECH ON SOCIAL MEDIA: INDONESIAN NETIZENS’ HATE COMMENTS OF PRESIDENTIAL TALK SHOWS ON YOUTUBE - Tahir, Ismail; Ramadhan, Muhammad Gana Fajar (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Hate comments on digital platforms, particularly social media, pose a significant threat to online investigations and present a complex issue for linguistic culture. Previous studies have mainly focused on the analysis of moderation strategies regarding this type of language use on the internet. In contrast, little attention has been given to identifying which hate comments on the internet are considered problematic. The current study investigates the phenomena of Indonesian netizens’ hate comments regarding the presidential election in 2024 on YouTube talk shows uploaded in 2023. By analyzing 315 datasets using Nvivo software, it shows that early warning (43%) is mostly employed by Indonesian netizens, followed by dehumanization and demonization (21%), violence and incitement (19%), and offensive language (17%) respectively. Moreover, it is found that anonymity and personality traits are the factors contributing to hate comments related to the 2024 presidential election. The factors influence Indonesian netizens in early-warning hate comments. The implications of the present study highlight the importance of examining the online behavior and language usage in online communication among Indonesian netizens. This understanding can help in mitigating hate comments on online platforms and in society as a whole.